Una statua in terracotta «selinuntina» ad Agrigento - Dario Giuliano (Les Carnets de l’ACoSt)
Since 2018, the Université Bordeaux-Montaigne has been engaged in research activities at the Chthonian sanctuary in Agrigento. In 2021, archaeological excavations were carried out in the “tempietto” to the east of Gate V and in the so-called “torrione” to the west of the aforementioned gate. From the latter, from a fill layer, comes the fragment presented here. It is a small portion of a female terracotta statue with well-preserved polychromy. It depict part of the right portion of the face, with fringed hair and short polos decorated with a meander motif. Stylistic study has revealed a strong selinuntine influence, although petrographic analysis has shown it to be a local production. It would therefore be the work of an itinerant craftsman who moved from Selinunte to Agrigento.